Mental health in the youth athlete - Daley, M. M.; Reardon, C. L. (Clinics in Sports Medicine, 2024)
Overtraining can result in depressed mood, fatigue, and physiologic and hormonal changes that perpetuate declines in performance, all of which can lead to burnout or withdrawal from sports.